Developments in renewable energies offshore : proceedings of the 4th International Conference on Renewable Energies Offshore (RENEW 2020), Lisbon, Portugal, 12-15 October 2020 - International Conference on Renewable Energies Offshore 2020 : Lisbon, Portugal); Soares, C. Guedes (Boca Raton : CRCPress/Balkema, 2021)
Developments in Renewable Energies Offshore contains the papers presented at the 4th International Conference on Renewable Energies Offshore (RENEW 2020, Lisbon, Portugal, 12 - 15 October 2020). The book covers a wide range of topics, including: resource assessment; wind energy; wave energy; tidal energy; ocean energy devices; multiuse platforms; PTO design; grid connection; economic assessment; materials and structural design; installation planning and maintenance planning. The book will be invaluable to professionals and academics involved or interested in Offshore Engineering, and Renewable and Wind Energy.
OCLC-licensed vendor bibliographic record.
Keywords: Ocean wave power -- Congresses; Tidal power -- Congresses; Renewable energy sources -- Congresses; TECHNOLOGY / General